A Qualitative Study Exploring the Causes of Boredom for Men with a Psychosis in a Forensic Setting. (2nd January 2018) - Bowser, Anita; Link, Wendy; Dickson, Mary; Collier, Lesley; Donovan-Hall, Maggie K.
ABSTRACT: Boredom is a problem in forensic mental health settings and is believed to increase levels of violence and be detrimental to health and recovery. There were 8 men in a forensic unit, all diagnosed with a psychotic disorder, that were interviewed regarding their experiences of boredom. A thematic analysis was used to identify emergent themes. These included: Mental health and motivation; Restrictive environment; Responsibilities; and Nothing to do. These findings provide a greater understanding of factors which may contribute to boredom within forensic settings and can guide occupational therapy interventions to address them.